Microvesicles as promising biological tools for diagnosis and therapy. (3rd October 2018) - Panfoli, Isabella; Santucci, Laura; Bruschi, Maurizio; Petretto, Andrea; Calzia, Daniela; Ramenghi, Luca A.; Ghiggeri, Gianmarco; Candiano, Giovanni
ABSTRACT: Introduction : Shed by most cells, in response to a myriad of stimuli, extracellular vesicles (EVs) carry proteins, lipids, and various nucleic acids. EVs encompass diverse subpopulations differing for biogenesis and content. Among these, microvesicles (MVs) derived from plasma membrane, are key regulators of physiopathological cellular processes including cancer, inflammation and infection. This review is unique in that it focuses specifically on the MVs as a mediator of information transfer. In fact, few proteomic studies have rigorously distinguished MVs from exosomes. Areas covered : Aim of this review is to discuss the proteomic analyses of the MVs. Many studies have examined mixed populations containing both exosomes and MVs. We discuss MVs' role in cell-specific interactions. We also show their emerging roles in therapy and diagnosis. Expert commentary : We see MVs as therapeutic tools for potential use in precision medicine. They may also have potential for allowing the identification of new biomarkers. MVs represent an invaluable tool for studying the cell of origin, which they closely represent, but it is critical to build a repository with data from MVs to deepen our understanding of their molecular repertoire and biological functions.